Interaction Between Persistent Organic Pollutants and C-reactive Protein in Estimating Insulin Resistance Among Non-diabetic Adults - Kim, Ki-Su (The Korean Society for Preventive Medicine, 2012)
OBJECTIVES: Chronic inflammation is now thought to play a key pathogenetic role in the associations of obesity with insulin resistance and diabetes. Based on our recent findings on persistent organic pollutants (POPs) including the lack of an association between obesity and either insulin resistance or diabetes prevalence among subjects with very low concentrations of POPs, we hypothesized that POP concentrations may be associated with inflammation and modify the associations between inflammation and insulin resistance in non-diabetic subjects. METHODS: Cross-sectional associations among serum POPs, C-reactive protein (CRP), and homeostasis model assessment of insulin resistance (HOMA-IR) were investigated in 748 non-diabetic participants aged ≥20 years. Nineteen types of POPs in 5 subclasses were selected because the POPs were detectable in ≥60% of the participants. RESULTS: Among the five subclasses of POPs, only organochlorine (OC) pesticides showed positive associations with CRP concentrations, while polychlorinated biphenyls (PCBs) showed inverse associations with CRP concentrations. There were statistically significant interactions between CRP and OC pesticides and between CRP and PCBs, in estimating HOMA-IR (P for interaction <0.01 and <0.01, respectively). CRP was not associated with HOMA-IR among subjects with low concentrations of OC pesticides or PCBs, while CRP was strongly associated with HOMA-IR among subjects with high concentrations of these POPs. CONCLUSIONS: In the current study, OC pesticides were associated with increased levels of CRP, a marker of inflammation, and both OC pesticides and PCBs may also modify the associations between CRP and insulin resistance.